2006
DOI: 10.1186/1472-6831-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of HIV infection in children and adults receiving highly active anti-retroviral therapy [HAART] in Dar es Salaam, Tanzania

Abstract: BackgroundThe aim of the study was to compare the prevalence and types of HIV-related oral lesions between children and adult Tanzanian patients on HAART with those not on HAART and to relate the occurrence of the lesions with anti-HIV drug regimen, clinical stage of HIV disease and CD4+ cell count.MethodsParticipants were 532 HIV infected patients, 51 children and 481 adults, 165 males and 367 females. Children were aged 2–17 years and adults 18 and 67 years. Participants were recruited consecutively at the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
95
5
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 32 publications
18
95
5
6
Order By: Relevance
“…OHL has rarely been described in the HIV-positive pediatric population, with a prevalence varying from 0 to 22.5%. Our results were in accordance with the literature 20,[22][23][24][25][26][27] . However, Grando et al described the EBV prevalence as being 56.43% in Brazilian children and 27.1% in the US children 2 .…”
Section: Discussionsupporting
confidence: 93%
“…OHL has rarely been described in the HIV-positive pediatric population, with a prevalence varying from 0 to 22.5%. Our results were in accordance with the literature 20,[22][23][24][25][26][27] . However, Grando et al described the EBV prevalence as being 56.43% in Brazilian children and 27.1% in the US children 2 .…”
Section: Discussionsupporting
confidence: 93%
“…En este estudio los pacientes tratados con monoterapia presentaron menos manifestaciones orales que aquellos tratados con biterapia con valores estadísticamente significativo, OR: 0,20, IC: 0,00-0,96 (p<0,02), difieren de Tappuni AR et al, que demostraron que los pacientes tratados con monoterapia tuvieron significativamente más lesiones orales que los sujetos de doble y triple terapia p<0,05 (13), Hamza OJ et al, reportaron que los pacientes adultos con más de un fármaco antirretroviral presentaron un riesgo significativamente menor de mostrar lesiones orales OR: 0,32; 95%, IC: 0,22-0,47 (p = 0,005) (20); dichas diferencias se podrían explicar ya que el número de la muestra de Tappuni AR et al y Hamza OJ et al, discrepa con la de este estudio; también que presentaron más alternativas de tratamiento farmacológico como combinaciones con tres fármacos y el número de pacientes incluidos en el grupo de monoterapia del presente estudio estaban en desproporción comparándolo con el grupo de biterapia, además en la fundación número 2 tenían un odontólogo dentro de la institución lo cual mejora las condiciones de salud oral ya que la asistencia odontológica es pronta y continua, algo que (22). Sin embargo en este estudio la candidiasis pseudomembranosa como manifestación oral asociada a VIH tiene menos probabilidades de presentarse cuando se tiene niveles de CD4 superiores a 500 cel./mm 3 mostrando valores estadísticamente significativos, con un OR: 0.297, IC: 0,103-0,852 (p<0,03).…”
Section: Discussionunclassified
“…The prevalence of oral thrush among Maasai women of reproductive age living in Ngorongoro Conservation Area was reported to be 32% [3]. This prevalence exceeded previous studies in immune-compromised populations which reported prevalence of 25% [4] and 23.5% [5] among HIV infected persons in Zambia and Tanzania respectively. In this study breastfeeding Maasai women had higher odds of getting oral thrush compared to the non-breastfeeding women [3].…”
Section: Introductionmentioning
confidence: 92%